2017
DOI: 10.1186/s12891-017-1608-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of bacterial and tuberculous spondylodiscitis with associated complications and non-infectious spinal pathology mimicking infections: a pictorial review

Abstract: Magnetic resonance (MR) imaging plays an important role in the evaluation of bacterial and tuberculous spondylodiscitis and associated complications. Owing to its high sensitivity and specificity, it is a powerful diagnostic tool in the early diagnosis of ongoing infections, and thus provides help in prompt initiation of appropriate, therapy which may be medical or surgical, by defining the extent of involvement and detection of complications such as epidural and paraspinal abscesses. More specifically, MR ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 32 publications
0
54
1
2
Order By: Relevance
“…Vertebral endplate destruction is typical for spondylodiscitis [21][22][23][24][25][27][28][29][30]. However, in this study, endplates in MT1, and early and advanced spondylodiscitis were found to be normal in up to 10.2%, 18.2%, and 5.7%, respectively.…”
Section: Discussioncontrasting
confidence: 70%
“…Vertebral endplate destruction is typical for spondylodiscitis [21][22][23][24][25][27][28][29][30]. However, in this study, endplates in MT1, and early and advanced spondylodiscitis were found to be normal in up to 10.2%, 18.2%, and 5.7%, respectively.…”
Section: Discussioncontrasting
confidence: 70%
“…Reports of spine amyloidomas are rare: 20 cervical, 20 thoracic, five lumbar, one cervicothoracic, and one thoracolumbar have been published. Cases of cervical amyloidoma are presented in Table .…”
Section: Discussionmentioning
confidence: 99%
“…Reports of spine amyloidomas are rare: 20 cervical, 12-31 20 thoracic, [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] five lumbar, 52-54 one cervicothoracic, 55 and one thoracolumbar 56 have been published. Cases of cervical amyloidoma are presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is difficult to determine whether water loss is due to daily activity and circadian (diurnal) rhythm (which is known to influence both water and height parameters) [ 22 ], or a water content drop in the ECM due to a loss of proteoglycans (PG’s) from the matrix and therewith the inability to retain water [ 23 25 ]. Finding matrix degeneration on T2w-images can also be obscured or mimicked by influx of fluids during an infectious or inflammatory process [ 26 ] or by the presence of free water in the lacunas of degraded ECM [ 27 ]. In addition, T2w- and PD-imaging are not informative of the discs’ mechanical (dys)function, or the cause of degeneration and pain [ 28 32 ].…”
Section: Introductionmentioning
confidence: 99%